UTICAJ BAZIČNO-MOTORIČKIH SPOSOBNOSTI NA REZULTATE SPOSOBNOSTI SPRINTERSKOG TRČANJA - Niko Raičković; Nataša Branković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The aim of this research was to determine the degree and characteristics of the link between sprinting sports results in the case of the 60 meter sprint and the basic-motor abi- lities of the elementary school students of the "Radojica Perović" elementary school, aged 13 ± 6 months. By means of a regressional analysis a statistically significant connection at the multivariate level between the set of basic-motor abilities and the 60 meter sprint was determined. At the univariate level, a statistically significant explanation of the 60 meter sprint results was determined in the case of the hand tapping variable (MTAP=0.04), the foot tapping variable (MTAN=0.02) and the squat variable (MČUČ=0.04). The obtained results point out that the examinees with better results in the hand tapping tests, the foot tapping and squat tests will achieve better results in the 60 meter sprint.